2015
DOI: 10.1002/macp.201500274
|View full text |Cite
|
Sign up to set email alerts
|

Biorenewable Thermoplastic Elastomeric Triblock Copolymers Containing Salicylic Acid‐Derived End‐Blocks and a Fatty Acid‐Derived Midblock

Abstract: A sustainable triblock copolymer thermoplastic elastomer is developed containing a fatty acid‐derived midblock and salicylic acid‐derived endblocks. The rubbery midblock, poly(lauryl methacrylate), is chosen for its low glass transition temperature, hydrophobicity, and degradation resistance. Poly(acetylsalicylic ethyl methacrylate), derived from salicylic acid, abundantly encountered in plant products such as fruit and vegetable components, is developed as a biorenewable alternative for the glassy endblocks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 89 publications
(141 reference statements)
0
29
0
Order By: Relevance
“…The microstructure and viscoelastic properties of the synthesized triblock copolymers were studied by DSC and dynamic mechanical thermal analysis (DMTA). DSC analysis of both synthesized triblocks revealed a low T g for the PBuLA midblock at about −20 • C, although no discernible signals corresponding to the T g of the glassy end blocks were observed, likely due to the lack of a DSC signal based on the low weight fraction of hard block (Figure S4) [9][10][11]14]. However, the presence of midblock T g near that of the homopolymer suggests that PBuLA segment is not mixed with either PIA or PVA segments.…”
Section: Aba Block Copolymers Characterization: Thermal Mechanical and Ahesive Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The microstructure and viscoelastic properties of the synthesized triblock copolymers were studied by DSC and dynamic mechanical thermal analysis (DMTA). DSC analysis of both synthesized triblocks revealed a low T g for the PBuLA midblock at about −20 • C, although no discernible signals corresponding to the T g of the glassy end blocks were observed, likely due to the lack of a DSC signal based on the low weight fraction of hard block (Figure S4) [9][10][11]14]. However, the presence of midblock T g near that of the homopolymer suggests that PBuLA segment is not mixed with either PIA or PVA segments.…”
Section: Aba Block Copolymers Characterization: Thermal Mechanical and Ahesive Propertiesmentioning
confidence: 99%
“…Making the most of reversible deactivation radical polymerizations techniques [8], the rich assortment of (meth)acrylate monomers from biosourced feedstocks offers an attractive palette of rubbery and glassy polymers for the design of innovative sustainable all-acrylic ABA-type thermoplastic elastomers (TPEs) with competitive properties. For instance, poly(lauryl methacrylate) (T g ≈ −46 • C) as the rubbery segment and poly(acetylsalicylic ethyl metacrylate) (T g ≈ 53 • C) as the glassy segment were combined to build up ABA copolymer architectures exhibiting elastomeric behavior at room temperature [9]. Biosourced acrylic monomers derived from glucose [10], isosorbide [11], itaconic acid imides [12] and rosin [13], as well as aromatic lignin derivatives [14], have been shown to provide useful glassy components for developing sustainable elastomeric and adhesive materials based on ABA block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent papers have focused on FA poly(meth)acrylates as sustainable sources to replace soft petro-sourced polydiene midblocks in the preparation of thermoplastic elastomers (TPE) owing to their various advantages. 134,162 Firstly, the use of saturated FA poly(meth)acrylate as midblock allows to overcome the limited oxidative stability and UV resistance of usual polydienes related to the unsaturated midblocks. 163,164 In addition, polymers resulting from FA derivatives display low glass transition temperature due to their long hydrophobic side chains and thus are suitable to provide a rubbery midblock in TPE triblock copolymer structures.…”
Section: Thermoplastic Elastomersmentioning
confidence: 99%
“…Taking advantage of the low FA-based (meth)acrylate monomers, Wang et al reported a promising triblock copolymer TPE containing lauryl acrylate-derived midblock (PLMA) and salicylic acid-derived end-blocks (PASEMA). The high incompatibility between PASEMA end-blocks with T g value close to 53 °C and PLMA midblock with low T g value (-47 °C) allowed a high degree of microphase separation between the rubbery and glassy phases which induced elastomeric behavior at room temperature 162.…”
mentioning
confidence: 99%
“…Biobased compounds do not have readily polymerizable double bonds, and therefore, they need to be modified to incorporate a polymerizable double bond in their structure. Numerous examples of this type of modification can be found in the literature. In particular, the incorporation of (meth)­acrylate moieties has been often reported using saccharides (glucose as the main example ), animal and vegetable fatty acids, and resin acids. …”
Section: Introductionmentioning
confidence: 99%